2014
DOI: 10.1016/j.compositesb.2013.12.055
|View full text |Cite
|
Sign up to set email alerts
|

Buckling and post-buckling of a composite C-section with cutout and flange reinforcement

Abstract: a b s t r a c tThis paper presents an investigation into the effect of cutout and flange reinforcement on the buckling and post-buckling behaviour of a carbon/epoxy composite C-section structure. The C-section having a cutout in the web is clamped at one end and subjected to a shear load at the other free end. Three different stiffener reinforcements were investigated in finite element analysis by using MSC Nastran. Buckling load was predicted by using both linear and nonlinear FE analysis. Experiments were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…The thickness of the lay‐up decreases during cure, so the magnetic pressure will increase gradually. According to the previously published literature, the thicknesses of the fabricated carbon fiber‐epoxy prepreg laminates for 8, 16, and 20 plies are ∼2.1–4.3 mm . Considering these thicknesses, the N38EH magnets are capable of generating a maximum pressure of 0.21–0.31 MPa (30–45 psi).…”
Section: Methodsmentioning
confidence: 97%
“…The thickness of the lay‐up decreases during cure, so the magnetic pressure will increase gradually. According to the previously published literature, the thicknesses of the fabricated carbon fiber‐epoxy prepreg laminates for 8, 16, and 20 plies are ∼2.1–4.3 mm . Considering these thicknesses, the N38EH magnets are capable of generating a maximum pressure of 0.21–0.31 MPa (30–45 psi).…”
Section: Methodsmentioning
confidence: 97%
“…F 5: , F 5; , F 6: , F 6; adalah kekuatan lamina longitudinal arah-1 dan transversal arah-2; F 7 adalah kekuatan geser dan G bernilai=-0.5 (Guo, et al, 2014) Nilai di bawah satu pada nilai indeks kegagalan menandakan struktur komposit tersebut aman ketika menerima beban. Sedangkan nilai satu menandakan tepat gagal dan nilai lebih dari satu menandakan kegagalan.…”
Section: Kriteria Kegagalanunclassified
“…Their research showed that it is possible to design and manufacture composite panels whose buckling and first-ply failure responses are insensitive to the existence of a central hole. Guo et al [17] studied composite C-section structure having circular and diamond shape cutout with flange reinforcements. They revealed that both cutout and reinforcement has little effect on the buckling stability of C-section structure.…”
Section: Introductionmentioning
confidence: 99%
“…From the above literature review, it was found that even though theoretical formulations of solving critical buckling loads of structures are successful [4,5] but plates with cutouts have got limitations [1][2][3]. Based on Finite Element formulations and experimental studies, plates with different cutout shapes [6][7][8][9][10][11][12][13][19][20][21][22][23][24][25][26][27][28][29] and reinforcements [15][16][17][18] were studied but comprehensive studies based on all major cutouts are notably limited. This paper addresses the effect of all major cutout shapes (circular, square, horizontal ellipse, vertical ellipse and diamond) and sizes, plate aspect ratio, ply thickness and fiber orientation angle on the buckling behavior of E-glass composite plate.…”
Section: Introductionmentioning
confidence: 99%